Students’ Perception Toward Code Switching Performed by Lecturer in Teaching Speaking - Sushy Teko Patanduk; Normalia Sirande; Matius Tandi Kombong (Universitas Cokroaminoto Palopo, 2021)
This research aims to investigate students’ perception toward code switching performed by lecturers in teaching speaking at English Education Study Program at UKI Toraja. Researchers used descriptive quantitative methods. The population of this research are the 6th semester students who have finished taking Speaking courses. Random sampling technique is used in sample selection with questionnaire as a tool to collect data. The results of the study were processed using quantitave by calculating the percentage of 10 items presented in the questionnaire. The result shows that students have positive perception toward code switching performed in teaching Speaking.